Isocoumarin, Thiaisocoumarin and Phosphaisocoumarin : natural occurrences, synthetic approaches and pharmaceutical applications - Pal, Sarbani (Elsevier, 2019)
Isocoumarin, Thiaisocoumarin and Phosphaisocoumarin: Natural Occurrences, Synthetic Approaches and Pharmaceutical Applications gives an overview of the various aspects of this class of heterocycle, with a major focus on synthesis and biological activity. Aromatic I lactones or isocoumarins with thiaisocoumarins, phosphaisocoumarins and a-pyranone fused with a heteroaryl ring constitute an important class of heterocyclic compounds. This book provides the methods applied for the synthesis of thiaisocoumarins, phosphaisocoumarins, and a-pyranone fused with a heteroaryl ring. It is useful to medicinal and natural product chemists who want to synthesize target molecules and develop cutting-edge technologies to provide better solutions to researchers. Features an overview of isocoumarins and their role in pharmaceutical researchPresents a template for the design, discovery and development of new and potential drugs in various therapeutic areasIncludes comprehensive coverage of the synthesis of isocoumarins, from traditional methods, to transition metal catalyzed methodsLooks at future applications for these important compounds in the areas of drug discovery and pharmaceutical research.